2017
DOI: 10.1136/bmjopen-2017-016494
|View full text |Cite|
|
Sign up to set email alerts
|

A qualitative study exploring the social and environmental context of recently acquired HIV infection among men who have sex with men in South-East England

Abstract: ObjectivesA key UK public health priority is to reduce HIV incidence among gay and other men who have sex with men (MSM). This study aimed to explore the social and environmental context in which new HIV infections occurred among MSM in London and Brighton in 2015.DesignA qualitative descriptive study, comprising in-depth interviews, was carried out as a substudy to the UK Register of HIV Seroconverters cohort: an observational cohort of individuals whose date of HIV seroconversion was well estimated. An induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…Participants described their sexual risk taking before initiating PrEP in the context of the sexualised use of drugs, geographical spaces linked with higher risk sexual norms, and digitised sexual networking. In a recent qualitative study in England, newly diagnosed MSM identified these same three factors, drug use, geographical space and digital networking, as part of a complex web of factors that influenced their risk behaviours and HIV acquisition [ 17 ]. There is a growing body of evidence on the sexualised use of drugs in the UK and associations with higher risk sexual behaviours including condomless sex, multiple partners and group sex [ 18 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants described their sexual risk taking before initiating PrEP in the context of the sexualised use of drugs, geographical spaces linked with higher risk sexual norms, and digitised sexual networking. In a recent qualitative study in England, newly diagnosed MSM identified these same three factors, drug use, geographical space and digital networking, as part of a complex web of factors that influenced their risk behaviours and HIV acquisition [ 17 ]. There is a growing body of evidence on the sexualised use of drugs in the UK and associations with higher risk sexual behaviours including condomless sex, multiple partners and group sex [ 18 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in MSM chemsexers, PrEP could act as a bridge for psychosocial follow-up, and constitutes a key element in a combined prevention strategy among high-risk MSM. 43 Some study limitations have to be acknowledged. First, the data used came from the IPERGAY trial, which only selected MSM who reported HIV high-risk behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…These intentions don't match the realities of too many unswayable people and those with low educational levels, marginalized, homeless people unless "control interventions" can be enforced. If the current HIV prevention concepts are to be modified, then differentiated insights into the behaviors of at-risk persons must be taken into account [116]. Sex in the context of social responsibility has to be addressed [117].…”
Section: Discussionmentioning
confidence: 99%